Русская литературная усадьба - Новиков Владимир Иванович (История. География. Этнография, 2012)
Экземпляры: ф.20 (2012) / Инвентарный номер: 48923 / Цена: / Сис.шифр: 83.3Р / Авт.знак: Н 73 / ББК: 83.3(2Рос=Рус)